2004
DOI: 10.1111/j.1469-8137.2004.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐specific expression and calcium activation of Arabidopsis thaliana phospholipase C isoforms

Abstract: Summary• PI-PLCs synthesise the calcium releasing second messenger IP 3 . We investigated the expression patterns of the Arabidopsis PI-PLC gene family and measured in vitro activity of encoded enzymes.• Gene specific RT-PCR and promoter-GUS fusions were used to analyse AtPLC gene expression patterns. The five available AtPLC cDNAs were expressed as fusion proteins in Escherichia coli .• All members of the AtPLC gene family were expressed in multiple organs of the plant. AtPLC1 , and AtPLC5 expression was loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 68 publications
6
111
0
1
Order By: Relevance
“…Our results show that inhibition of PLC activity in plant roots blocks the increase in cytosolic IP 3 and Ca 2+ levels in response to nitrate treatments. In addition, LaCl 3 also blocked the increase in IP 3 and [Ca 2+ ] cyt levels by nitrate treatments, suggesting a calcium-dependent PLC activity (Hunt et al, 2004). These results support the idea that one or more PLCs are implicated in Arabidopsis root nitrate signaling.…”
Section: Discussionsupporting
confidence: 77%
“…Our results show that inhibition of PLC activity in plant roots blocks the increase in cytosolic IP 3 and Ca 2+ levels in response to nitrate treatments. In addition, LaCl 3 also blocked the increase in IP 3 and [Ca 2+ ] cyt levels by nitrate treatments, suggesting a calcium-dependent PLC activity (Hunt et al, 2004). These results support the idea that one or more PLCs are implicated in Arabidopsis root nitrate signaling.…”
Section: Discussionsupporting
confidence: 77%
“…Nt PLC3 is also highly similar to lily (Lilium daviddi) pollen PI-PLCs (Ld PLC1 and Ld PLC2, 53.6 and 53.7% identical amino acids, respectively; Pan et al, 2005) as well as to Arabidopsis At PLC4, At PLC5, and At PLC7 (51.1 to 66.0% identical amino acids; Mueller-Roeber and Pical, 2002), which are preferentially expressed in pollen based on microarray data (Zimmermann et al, 2004) and promoter-b-glucuronidase (GUS) fusion analysis (Hunt et al, 2004). Interestingly, phylogenetic analysis showed that pollen PI-PLCs cluster into two clearly distinct groups composed of Nt PLC3, Pet PLC1, and At PLC7 and of Ld PLC1, Ld PLC2, At PLC4, and At PLC5 (see Supplemental Figure 2 online).…”
Section: Nt Plc3 Is Homologous With Characterized Plant and Animal Pimentioning
confidence: 98%
“…Three PI-PLC isoforms are preferentially expressed in Arabidopsis pollen and pollen tubes based on microarray and promoter-GUS fusion analysis (see above) (Hunt et al, 2004;Zimmermann et al, 2004). The relative contributions of these three isoforms to the PI-PLC activity in Arabidopsis pollen tubes remain to be determined, as available data do not allow quantitative comparison of gene expression levels or protein activities.…”
Section: Nt Plc3 Is a Major Pi-plc Isoform In Tobacco Pollen Tubesmentioning
confidence: 99%
“…Yet, as in mammalian cells, all PI-PLC activities and proteins examined so far in plant cells were found to be predominantly localized in the plasma membrane (PM). [18][19][20] On the other hand, AtPI4KIIIα1 expressed in insect cells has been observed in perinuclear membranes which may correspond to the endoplasmic reticulum (ER). 20 As to AtPI4KIIIβs they are recruited to the trans-Golgi network (TGN) in Arabidopsis root hair 22 and may also localize at the plasma membrane, 23 in the nucleus 24 and/or in small cytoplasmic vesicles.…”
Section: Eat In or Take Away?mentioning
confidence: 99%